Palmar and Plantar Erythrodysesthesia in Patient as a Late Cutaneous Manifestation of COVID-19 Infection (Revista de Medicina Clinica, 2022)
Clinical Snapshot on "Palmar and Plantar Erythrodysesthesia in Patient as a Late Cutaneous Manifestation of COVID-19 Infection" presented in Volume 6 Issue 3 of Revista de Medicina Clínica.
Keywords: Erythrodysesthesia; COVID-19; SARS-CoV-2